2015
DOI: 10.23939/chcht09.02.257
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Properties of Petroleum Sludge Produced at the Refineries

Abstract: Abstract. Petroleum sludge composition and physicochemical characteristic and thermal stability of its organic matter have been investigated. The regularities of sludge layers distribution in the storage ponds have been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Organics solids compose 90 % of the sludge material, which characterized as hydrocarbons, asphaltenes, and paraffin. Inorganic solids can be characterized as sand, iron sulfides and iron oxides [28]. Cooling the crude oil below the cloud point, mixing with incompatible materials, and Fig.…”
Section: Petroleum Sludgementioning
confidence: 99%
“…Organics solids compose 90 % of the sludge material, which characterized as hydrocarbons, asphaltenes, and paraffin. Inorganic solids can be characterized as sand, iron sulfides and iron oxides [28]. Cooling the crude oil below the cloud point, mixing with incompatible materials, and Fig.…”
Section: Petroleum Sludgementioning
confidence: 99%
“…The landfill contains oil residues recovered during the cleaning of tanks for the transportation of crude oil from the fields of the Mangyshlak Peninsula. A study of similar landfills carried out by the authors of (Vdovenko et. al., 2015) showed that oil residues contained in landfills is subject to layer-by-layer phase separation.…”
Section: Characterization Of Oil Residuesmentioning
confidence: 99%
“…The production of dangerous waste product generated by the petroleum industries in significant amount of sludge leads to the environmental pollution [5]. The sludge has the capability to pass through the ground and contaminate the soil, water and air [2]. Based on the studies, some of the polycyclic aromatic hydrocarbons (PAHs) which present in PS are shown in Fig 1 and detailed description of the hydrocarbons are illustrated in Table 1 [6].…”
Section: A Polycyclic Aromatic Hydrocarbon Content Of Petroleum Sludgementioning
confidence: 99%
“…The composition of PS is different hinge on the inception and storage state. PS is generally classified as a complex and stable emulsion-suspension system, with polycyclic aromatic hydrocarbons (PAH) and heavy metals [2]. Aliphatic and aromatics are the two major fractions of the sludge as it accounts up to 75% of the total content.…”
Section: Introductionmentioning
confidence: 99%